2019
DOI: 10.1097/mcg.0000000000001242
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Combination of Pinaverium Bromide 100 mg Plus Simethicone 300 mg in Abdominal Pain and Bloating in Irritable Bowel Syndrome: A Randomized, Placebo-controlled Trial

Abstract: Goals: We aimed to evaluate the efficacy and safety of PB+S (pinaverium bromide 100 mg plus simethicone 300 mg) in patients with irritable bowel syndrome (IBS). Background: IBS is a multifactorial disorder; thus, combination therapy with different mechanisms of action is expected to be useful. PB+S has shown effectiveness in an open-label clinical study in IBS. However, there are no placebo-controlled trials. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
14
0
3
Order By: Relevance
“…Simethicone, also known as activated dimethicone, is an antifoaming agent. It prevents bubble formation and gas retention, which alleviates abdominal pain and bloating; therefore, it is widely prescribed to patients with irritable bowel syndrome . Several recent randomized controlled trials have demonstrated that addition of SIM to bowel preparation regimens can help improve the quality of bowel preparation, ADR and patient tolerance .…”
Section: Discussionmentioning
confidence: 99%
“…Simethicone, also known as activated dimethicone, is an antifoaming agent. It prevents bubble formation and gas retention, which alleviates abdominal pain and bloating; therefore, it is widely prescribed to patients with irritable bowel syndrome . Several recent randomized controlled trials have demonstrated that addition of SIM to bowel preparation regimens can help improve the quality of bowel preparation, ADR and patient tolerance .…”
Section: Discussionmentioning
confidence: 99%
“…The most common AEs reported were nausea, dizziness, abdominal discomfort, and hypertension ( 15 ). Schmulson reported that the combination of pinaverium 100 mg plus simethicone 300 mg twice daily compared with placebo significantly improved the intensity of abdominal pain ( P = 0.04) and bloating ( P = 0.02); the individual contribution of each agent cannot be determined ( 59 ). The safety profile of pinaverium/simethicone was generally comparable with that of placebo.…”
Section: Resultsmentioning
confidence: 99%
“…The high placebo response observed in 1 study was potentially because of patient selection and/or the patient-provider relationship ( 54 ). Pinaverium was examined in 5 randomized, placebo-controlled studies that differed in treatment duration, dosing, and outcomes; furthermore, 1 study included only patients with IBS-D ( 15 , 56 – 59 ). Studies generally had an unclear risk of bias ( 15 , 56 – 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…81 A prospective, randomized, placebo controlled trial in patients with IBS (Rome III criteria; n ¼ 285) found that the combination of pinaverium bromide and simethicone was more effective at relieving symptoms of abdominal pain and bloating than placebo. 82…”
Section: Antispasmodicsmentioning
confidence: 99%